Physical and computational modeling for finite element analysis - Che Muda, Zakaria (1988)
In the past, the majority of papers relating to F.E analysis were related to the development of new special elements and the computational algorithms for equation or eigenvalue solutions. Although more efforts has been made recently in making program user orientated yet answer to the proper discretization of the model and its application is left to the responsibility of the user. Where is the occasional or inexperienced user going to obtain the necessary guidelines for implementing his or her analysis? This paper aim to provide the occasional user a general guidelines for some aspect of physical and computational finite element modelling for implementing his or her analysis.